Quantifying Mycobacterium tuberculosis Transmission Dynamics Across Global Settings: A Systematic Analysis. Issue 1 (13th October 2022) - Smith, Jonathan P; Cohen, Ted; Dowdy, David; Shrestha, Sourya; Gandhi, Neel R; Hill, Andrew N
Abstract: The degree to which individual heterogeneity in the production of secondary cases ("superspreading") affects tuberculosis (TB) transmission has not been systematically studied. We searched for population-based or surveillance studies in which whole genome sequencing was used to estimate TB transmission and in which the size distributions of putative TB transmission clusters were enumerated. We fitted cluster-size–distribution data to a negative binomial branching process model to jointly infer the transmission parameters R (the reproduction number) and the dispersion parameter, k, which quantifies the propensity of superspreading in a population (generally, lower values of k (<1.0 ) suggest increased heterogeneity). Of 4, 796 citations identified in our initial search, 9 studies from 8 global settings met the inclusion criteria ( n = 5 studies of all TB; n = 4 studies of drug-resistant TB). Estimated R values (range, 0.10–0.73) were below 1.0, consistent with declining epidemics in the included settings; estimated k values were well below 1.0 (range, 0.02–0.48), indicating the presence of substantial individual-level heterogeneity in transmission across all settings. We estimated that a minority of cases (range, 2%–31%) drive the majority (80%) of ongoing TB transmission at the population level. Identifying sources of heterogeneity and accounting for them in TB control may have a considerable impact on mitigating TB transmission.